PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN VIDEO INSPIRATIF TERHADAP SOCIAL EMOTIONAL LEARNING (SEL) DI SEKOLAH DASAR - Lintang Putri Hidayanti; Esmi Tsalsa Sofiawati; Rahmatika Layyinah; Melia Marsanda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low social and emotional skills of elementary school students, evident from limited cooperation, empathy, and emotional regulation during learning, particularly in Civics Education on the topic of rights and obligations. This study aimed to examine the implementation and effect of the Problem Based Learning (PBL) model assisted by inspirational videos on students' Social Emotional Learning (SEL). A quantitative approach with a one-group pretest-posttest design was employed. The population consisted of all 274 students of SDN Ranji, with a sample of 33 sixth-grade students selected through purposive sampling. Data were collected using observation sheets and an SEL instrument, then analyzed through normality tests, homogeneity tests, and hypothesis testing using a Paired Sample t-Test. The results showed that the PBL model assisted by inspirational videos was implemented across five sessions following the five stages of PBL, and successfully increased students' emotional engagement and active participation. The pretest mean score of 27.21 increased significantly in the posttest, with the highest frequencies falling in the 40–44 (30%) and 45–49 (27%) intervals. The Paired Sample t-Test yielded a t-value of 20.626 with a significance level of 0.000 (< 0.05), leading to the rejection of H₀ and acceptance of H₁. It can therefore be concluded that the PBL model assisted by inspirational videos has a significant effect on the SEL of sixth-grade students at SDN Ranji, covering all SEL components according to the CASEL framework: self-awareness, self-management, social awareness, relationship skills, and responsible decision-making.